The principle of preserve sibling relationships: the peruvian administrative adoption - Salas Pastor, Gladys Patricia (2022)
Legislative Decree No. 1297 established, for the first time, the principle of preserving sibling relationships. In this regard, this research is aimed at deepening in the development of this innovative principle. Knowing what this principle entails for their legal situation will greatly benefit sibling groups placed for adoption. In that sense, the purpose is to know the current situation of the principle of preserving sibling relationships and determining its consequences on sibling groups placed for adoption. In this quest, we have used the historical and deductive methodology as well as the dogmatic method. We conclude there are some progress in regulations in Peru, but there are still aspects that need to be further specified in order to ensure sibling relationships between the members of a sibling’ group.